Obnoxious environmental pollutant, the parthenium weed : a possibility of ecological disaster in Malaysia - S.M. Rezaul Karim (2013)
Parthenium weed (Parthenium hysterophorus) is an invasive weed and environmental pollutant in many countries including Mexico, India, Sri Lanka, Nepal, Pakistan, Bangladesh, Ethyopia, Tanzania, Kenya, Australia etc. It causes enormous losses to human health by making allergenic diseases, hay fever, eczima, respiratory problems etc. Animal health are also affected due to allergic swollenness of mouth, ulceration and stomach toxicity. The meat and milk of the cows became non-usable due to unwanted odour and taste. Many upland crops like maize, wheat, barley, upland rice, vegetables, spices etc. are infested with the weed, while it reduces the crop yield and quality. Biodiversity of the infested area is also affected due to its colonial growth habit and very fast growth rate. India and Australia are the severely affected countries in the world, where a lot of efforts and money are being spent every year to combat this menace. Although Malaysia is not infested with this obnoxious weed yet but the edaphic and climatic conditions of the country indicate that those conditions may favour to establish the weed if the peoples of the country are not alert about the invasion of the weed from the weed-infested countries. Awareness must be created among the inhabitants of the country to get rid of this probable ecological disaster.